Crystallization of the Lys49 PLA2 homologue, myotoxin II, from the venom of Atropoides nummifer - Watanabe, Leandra (2004)
Myotoxin II, a Lys49 catalytically inactive phospholipase A2 homologue from Atropoides nummifer venom, was purified, characterized and crystallized. The crystals belongs to the tetragonal system, space group P43212, with unit cell parameters (a=b=68.66 and c=63.87 2). Diffraction data were collected to a resolution of 2.32 2. The crystal structure is currently being determined using molecular replacement techniques.